PERANCANGAN DESAIN MOTIF BATIK KONTEMPORER PEKALONGAN GUNA MEMPERKAYA MOTIF BATIK BERDASARKAN ORNAMEN LOGO KOTA PEKALONGAN - Anzilirohmania Kirana; Azzriel Fala Ananta; Abi Senoprabowo (AKSA: Jurnal Desain Komunikasi Visual, 2021)
The existence of Pekalongan batik has no doubt about its existence where the characteristics or characters on the motif have a strong image, but some classic batik motifs are more identical with adults. So this design aims to develop contemporary batik motifs adapted from the Pekalongan City logo but still suitable for young people. The use of the Pekalongan City logo itself means that there is still no motif adapted from the ornament on the logo. This design was compiled using the theoretical method of the creative art creation process from Gustami which has three stages. The first is the exploration process, which is the idea-searching stage, followed by collecting and searching for data about the meaning of the Pekalongan City logo. The second process of designing works, generating ideas and ideas are obtained from the brainstorming process. The third embodiment process, including the final design and mockup. The results of the design development in the form of designs can be applied to fabrics, masks, tote bags, and pillowcases that have been adapted to the target audience. Through the results of batik motifs is a first step to invite people to know, love, and preserve the traditions of our nation.